2021
DOI: 10.1530/rep-20-0272
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of the E SRRG pathway in placental dysfunction

Abstract: Normal placental development and function is of key importance to fetal growth. Conversely aberrations of placental structure and function are evident in pregnancy complications including fetal growth restriction (FGR) and preeclampsia. Although trophoblast turnover and function is altered in these conditions, their underlying aetiologies and pathophysiology remains unclear, which hampers development of therapeutic interventions. Here we review evidence that supports a role for Estrogen Related Receptor-gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…As a special organ for the communication between the fetus and the mother, the placenta has the functions of material transport, endocrine, and barrier, which are essential for fetal survival and development 87 . The impaired placental function can lead to IUGR 88 , and IUGR individuals exhibit multiple organ dysplasia 89 . It has been shown that some drugs may indirectly induce multi-organ developmental toxicity by affecting the functional development of the placenta.…”
Section: Multi-organ Developmental Toxicity In Offspring Induced By M...mentioning
confidence: 99%
“…As a special organ for the communication between the fetus and the mother, the placenta has the functions of material transport, endocrine, and barrier, which are essential for fetal survival and development 87 . The impaired placental function can lead to IUGR 88 , and IUGR individuals exhibit multiple organ dysplasia 89 . It has been shown that some drugs may indirectly induce multi-organ developmental toxicity by affecting the functional development of the placenta.…”
Section: Multi-organ Developmental Toxicity In Offspring Induced By M...mentioning
confidence: 99%
“…Studies have reported differences in the etiology of early and late-onset preeclampsia [ 41 , 42 ], as well as varying risks of adverse outcomes associated with the timing of exposure [ 43 , 44 ]. Early-onset preeclampsia may be driven by placental dysfunction [ 45 ], which occurs when a placental abnormality restricts blood flow, potentially due to suppression of estrogen-related receptor-gamma leading to vascular abnormalities [ 46 ]. Late-onset preeclampsia could be primarily a maternal hypertensive condition [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our ultimate aim is to understand the mechanisms underlying placental dysfunction observed in FGR, with a particular focus on the role of ESRRG [ 95 ]. The sex-specific effects of BPA on ESRRG signaling we observed might begin to provide a biological explanation for the observed relationship between low fetal weight in male neonates and maternal BPA exposure seen in epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%